Use of mobile applications to improve nutrition behaviour: A systematic review. (August 2020) - Paramastri, Rathi; Pratama, Satwika Arya; Ho, Dang Khanh Ngan; Purnamasari, Sintha Dewi; Mohammed, Afrah Zaki; Galvin, Cooper J; Hsu, Yi-Hsin Elsa; Tanweer, Afifa; Humayun, Ayesha; Househ, Mowafa; Iqbal, Usman
Highlights: Updated review of mobile technology for nutritional behavior change Mobile app-based interventions can be useful for improving healthy behaviors related to diet and physical activity. Some mobile applications appear to be effective for nutrition education and as knowledge resources. Specific suggestions for testing these new tools for health promotion in more diverse populations and standardizing efficacy measurements. Abstract: Background and Objective: Mobile applications could be effectively used for dietary intake assessment, physical activity monitoring, behavior improvement, and nutrition education. The aim of this review is to determine the effectiveness of mobile applications in improving nutrition behaviors through a systematic review of literature. Methods: The review protocol was registered with PROSPERO: registration number CRD42018118809, and followed PRISMA guidelines. We involved original articles including mobile electronic devices for improving dietary intake, physical activity, and weight management in adult populations in this review. Data were retrieved from January 2010 to December 2018 with PubMed, Web of Science, Excerpta Medica Database (Embase), and Cumulative Index to Nursing and Allied Health Literature (CINAHL) as data sources. Authors individually screened the titles and abstracts, then full articles in order to obtain papers that met inclusion criteria. Results: The database search yielded 2962 records. After removing the duplicates and analyzing the full text papers a total of 8 original articles were reviewed. Two articles showed obvious bias and were not included in our results or discussion. The remaining six articles with low to moderate bias risk were included in this systematic review. Three selected studies were randomized control trials (RCTs) with over 180 participants each. The other three studies were a nested trial, a case-control trial, and a pilot RCT with 36, 162, and 24 participants respectively. All larger RCTs and the small case control trail showed significant improvements in some nutritional-health objectives measured. The other two trials showed insignificant improvements in outcomes measured between groups. Conclusion: This study highlights the potential significant health benefits acquirable through mobile health application-assisted nutrition interventions. Some of these studies required significant financial and time input from providers for the application's utilization. Further studies, perhaps with multiple intervention arms, are required to compare across programs the elements that are essential for health benefits observed.